The dressmakers of Prospect Heights : a novel - Zeldis, Kitty (Harper, an imprint of HarperCollins Publishers, 2022)
"For fans of Fiona Davis, Beatriz Williams, and Joanna Goodman, a mesmerizing historical novel from the bestselling author of Not Our Kind about three women in post-World War I New York City and the secrets they hold. Brooklyn 1919. As New York City continues to reel from the losses of both World War I and the deadly influenza epidemic, the lives of three very different women are about to take an unexpected turn. Recently arrived from New Orleans, Beatrice is trying to establish her dress shop with help from Alice, a teenaged orphan she brought north with her, while their neighbor, newlywed Catherine, longs for a baby she cannot seem to conceive. When Bea befriends Catherine and the two start to become close, Alice feels left out of their bond. In her search for a family of her own, she'll set into motion a series of events that will make all three women confront painful secrets from the past in order to envision a better future. Moving from the bustling streets of Brooklyn and Manhattan to late 19th century Russia and the lively quarters of New Orleans, Two Daughters is a story of female friendship, the families we are born into and the families we make, and how some bonds can be tested but never broken"--